PENGEMBANGAN LEAFLETPERMEN JELLY NANAS PADA SUB MATERI PERAN TUMBUHAN DI BIDANG EKONOMI - Hendiko, Martin; Daningsih, Entin; Yokhebed, Yokhebed (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aimed to determine the feasibility of leaflet for making pineapple jelly candy in the sub-material role of plants in the economy and students' response to leaflet for making pineapple jelly candy.This research uses Research & Development method which sixout of ten stages namely potential and problems, data collection, product design, design validation, design revision, and limited trial.Questionnaireswere validated by one biology teachers andlecturers.The data were analyzed using Lawshe methode. Leaflet obtaineded CVI value of 0,96 and categorized as valid there for it was feasible to be use as a learning media. In edition students responsed very high 84%to leaflet media.Keywords: feasibility,leaflets,pineapple jelly candy,research and development methode, and student response.